Plasma Brain-Derived Neurotrophic Factor Levels in Newborn Infants with Neonatal Abstinence Syndrome - Subedi, Lochan; Huang, Hong; Pant, Amrita; Westgate, Philip M.; Bada, Henrietta S.; Bauer, John A.; Giannone, Peter J.; Sithisarn, Thitinart (Frontiers in Pediatrics, 2017)
Background: Brain derived neurotrophic factor (BDNF) is a type of growth factor that promotes growth and survival of neurons. Fetal exposure to opiates can lead to postnatal withdrawal syndrome, which is referred as neonatal abstinence syndrome (NAS). Preclinical and clinical studies have shown an association between opiates exposure and alteration in BDNF expression in the brain and serum levels in adult. However, to date there are no data available on the effects of opiate exposure on BDNF levels in infant who are exposed to opiates in utero and whether BDNF level may correlate with the severity of NAS. Objective: To compare plasma BDNF levels among NAS and non-NAS infants and to determine the correlation of BDNF levels and the severity of NAS. Methods: This is a prospective cohort study with no intervention involved. Infants ≥35 weeks of gestation were enrolled. BDNF level was measured using ELISA technique from blood samples drawn within 48 hours of life. The severity of NAS was determined by the length of hospital stay, number of medications required to treat NAS. Results: 67 infants were enrolled, 34 NAS and 33 non-NAS. Mean gestational age did not differ between the two groups. Mean birth weight of NAS infants was significantly lower than the non-NAS infants (3070±523 grams vs. 3340±459 grams, p=0.028). Mean BDNF level in NAS group was 252.2±91.6 ng/ml, significantly higher than 211.3±66.3 ng/ml in the non-NAS group (p=0.04). There were no differences in BDNF levels between NAS infants that required one medication versus more than one medication (254±91 vs. 218±106 ng/ml, p=0.47). There was no correlation between the BDNF levels and length of hospital stay (p=0.68) among NAS infants. Overall there were no significant correlation between BDNF levels and NAS scores except at around 15 hours after admission (correlation 0.35, p=0.045). Conclusion(s): Plasma BDNF level was significantly increased in NAS infants during the first 48 hours when compared to non-NAS infants. The correlations between plasma BDNF levels and the severity of NAS warrant further study. These results suggest that BDNF may play a neuromodulatory role during withdrawal after in utero opiate exposure.